Mental model of a medieval scribe as a basic engine concept for an intelligent, bibliophilic book design system - Szczurek, Bogdan; Szuba, Tadeusz (Journal of Print and Media Technology Research, 2023)
This paper presents the current state of the research project which aims to build a mental model of an abstract medieval scribe. It will be the basis for the design of a novel intelligent engine for a book design system enabling to easily create books of exceptional artistic and bibliophilic value. A page of a book filled with illustrations, ornaments and text can be considered as an extension of the idea of a Turing Machine infinite tape. From this point of view, a mental model of a scribe can be considered as an extension of Alan Turing’s concept of an abstract clerk-mathematician, processing a tape according to this tape’s contents and the contents of his brain serving as a control module. Thus, authors want to expand the concept of the Turing Machine to design a model of an abstract medieval scribe and to use it as a basis for a future desktop publishing system. Joint knowledge of the authors on the practice of bibliophilic book edition and on the theory of artificial intelligence and expert systems provides a real chance that this project will be completed and implemented. This paper presents the basic theoretical foundations of the project.